Nursing Staff Insight about Modifiable Risk Factors of Cardiovascular Diseases in a Multicultural Setting, Saudi Arabia - Alqirnas, Anfal; Alotaiby, Shahad; Alfaqeeri , Munira; Alsaran, Hadel; Sami, Waqas (Progress in Nutrition, 2022)
OBJECTIVE: Cardiovascular diseases (CVDs) are a group of disorders of the heart and blood vessels that occur due to different risk factors. studies had shown that controlling these factors can result in lower mortality rate. Therefore, the objective of this study was to investigate the attitude, knowledge, and practice regarding cardiovascular modifiable risk factors among nursing staff in a tertiary hospital in Riyadh.MATERIALS AND METHODS:  A cross-sectional study was conducted between January 2020 – October 2020 in King Salman Heart Center at King Fahad Medical City (KFMC). Data were obtained utilizing a self-administered questionnaire completed by 121 nurses. Analysis of the data was done using IBM SPSS version 26 (IBM Corp., Armonk, NY, USA).RESULTS: The majority of the participants did not have any CVDs' risk factors. However, physical inactivity, obesity, unhealthy eating, and smoking were frequent in a substantial number of the participants. It was found that 71.07% of nurses had good knowledge, a positive attitude (61.98%), and most of them were following a fair nursing practice (67.77%).CONCLUSION: Overall, we found that the participating nurses had a good knowledge, fair attitude and good practice about the modifiable risk factors of CVD which urges launching initiatives for CVD risk prevention in KFMC, however, awareness campaigns are recommended to educate the nurses more with the state-of-the-art knowledge in this area.